Effects of HRV biofeedback training on recovery, stress management, reaction time and concentration in competitive rowing – preliminary study - Zuzanna Myszka; Maria Wolff; Piotr Basta; Dariusz Kozłowski (European Journal of Translational and Clinical Medicine)
Background: Our aim was to determine the effect of HRV biofeedback (HRVB) training on psychophysiological factors, e.g. reaction time, stress management and concentration during the starting period in competitive rowing. Material and methods: 12 senior national team rowers aged 20-40 (both men and women) were assigned to an experimental (n = 6) and a control (n = 6) group. The experimental group performed HRVB training for 4 weeks, for 20 minutes, twice a day. The control group did not perform any respiratory training. Parameters such as reaction time, resting breathing rate, concentration, subjective stress and heart rate variability were evaluated during the pre-test, post-test and post-post test phases. Results: We noted an improvement in reaction time in the experimental group after HRVB training (pre-test 63.8 sec to post-post test 58.8 sec) and no significant statistical differences in the control group, as well as a statistically significant reduction in resting respiratory rate frequency in the experimental group in comparison to the control group in the post-test (p = 0.0398). Other analyses did not exceed the threshold for statistical significance. Conclusions: Our results suggest that HRVB training may reduce the resting respiratory rate in the experimental group and may improve the reaction time of rowers.